Nurses' Experiences of Communicating With Hospitalized, Suddenly Speechless Patients. (February 2015) - Rodriguez, Carmen S.; Spring, Heather J.; Rowe, Meredeth
We used a qualitative focus group design to explore the experiences and challenges of nurses who work with hospitalized patients experiencing the sudden inability to verbalize their needs, also known as sudden speechlessness. In response to open-ended questions in facilitated focus groups, 18 nurses discussed issues around the care and communication needs of suddenly speechless (SS) patients. Nurses identified multiple, commonly occurring communication challenges when caring for SS patients. They believed these challenges led to poorer recognition of patient needs, with the potential for compromised patient care. Nurses described how the lack of reliable strategies to facilitate communication sometimes resulted in negative patient outcomes, including unmet psychosocial needs and the potential that informed consent and educational issues were being inadequately addressed for the SS patients. Even experienced nurses indicated ongoing problems in communicating with SS patients, despite using a multitude of strategies, leaving many to deal with issues of frustration and role conflict.